The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3892/etm.2020.9440
|View full text |Cite
|
Sign up to set email alerts
|

The expression and clinical significance of three lncRNAs in patients with a missed abortion

Abstract: Missed abortions are common complications that occur in early pregnancy, and impaired trophoblast functions have been indicated to be associated with their pathogenesis. The long noncoding RNAs (lncRNAs) Metastasis Associated Lung Adenocarcinoma Transcript 1 ( MALAT1) , HOX Transcript Antisense RNA ( HOTAIR) and Maternally expressed gene 3 ( MEG3) have been demonstrated to serve a crucial regulatory role in the mobility of trophoblast cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Luo et al exhibited higher expression of HOTAIR in RSA patients compared with healthy controls 63 . Interestingly, it is reported that HOTAIR can be suppressed in RSA 64 .…”
Section: Discussionmentioning
confidence: 96%
“…Luo et al exhibited higher expression of HOTAIR in RSA patients compared with healthy controls 63 . Interestingly, it is reported that HOTAIR can be suppressed in RSA 64 .…”
Section: Discussionmentioning
confidence: 96%
“…Missed abortion is a special type of spontaneous abortion which accompany serious complication endanger the reproductive healthy [20]. Previous studies on missed abortion focused on chromosome abnormalities [21], uterine artery blood ow resistance, angiogenesis [22], immune in ammationrelated [23,24], etc. In recent years, with the further study of the human microbiome, researchers gradually realized that from the surface of human body to the intestinal ora, all of them have an impact on the ecological balance of human body and the occurrence and development of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs modulate a wide variety of biological processes, such as cellular differentiation, maintenance of stem cell pluripotency, and development of tissues and organs, contributing to the onset of human diseases [ 17 , 43 ]. They are implicated in different pregnancy-related complications, including preeclampsia [ 44 ], GDM [ 45 ], intrauterine growth restriction (IUGR) [ 46 ], and missed abortions [ 47 ].…”
Section: Ncrnas As Potential Biomarkersmentioning
confidence: 99%